THE INFLUENCE OF ORGANIZATIONAL COMMITMENT AND ISLAMIC WORK ETHIC TOWARD JOB PERFORMANCE OF TEACHING STAFF AT UNIVERSITIES IN SURAKARTA WITH INSTITUTIONAL BASE AS A MODERATOR VARIABLE - Wahyudi, Amin (PROCEEDING INTERNASIONAL SEMINAR, 2015)
The purposes of this study are: (1) examine the impact of organizational commitment to job performance of faculty member in Surakarta; (2) examine the impact of Islamic work ethic to job performance; and (3) examine the mediating role of institutional-base on the impact of Islamic work ethic to job performance. The results show that organizational commitment and Islamic work ethic had significance effect to job performance, but institutional-based had no moderating role in the effect of Islamic work ethic to job performance.Keywords: organizational commitment, Islamic work ethic, job performance, institusional-based.